A STUDY OF AN ALGORITHM FOR THE CONSTRUCTION OF SURFACES DEFINED GRAPHICALLY BY CURVES APPLIED IN THE ARCHITECTURAL ENVIRONMENT (Innovation in Woodworking Industry and Engineering design, 2026)
The aim of the present research is the construction of graphic surfaces defined by sections with parallel planes or by the points coordinates of the network nodes. To achieve the set goal, an algorithm for constructing 2 and 3 images of graphical surfaces, defined by curves, has been investigated. An approbation of the algorithm is also presented along with its application in an architectural environment.